Nilai-Nilai Pendidikan Karakter Tokoh Dalam Novel Gunung Ungaran Karya Nh. Dini - Wahyu Handila Suci; Titiek Fujita Yusandra; Ricci Gemarni Tatalia (STKIP PGRI Sumatera Barat, 2021)
This research was motivated by the problem of being able to find the values of character education in the novel Gunung Ungaran by Nh. Dini. The purpose of this study is to describe the values of character education in the novel Gunung Ungaran by Nh. Dini. This research is a qualitative research using content analysis method. The object of this research is the novel Gunung Ungaran by Nh. Dini. The data in this study are words, phrases, sentences and discourses which are the values of character education. The data source in this research is the novel Gunung Ungaran by Nh. Dini. The data techniques used are reading novels, marking data related to the value of character education, recording data, making inventory, and classifying. The results of this study indicate that there are ten values of character education found in the novel Gunung Ungaran. In addition to the value of character education, other character education values are also found, such as: 1) religious, 2) Tolerance, 3) Work hard, 4) Independent, 5) Curiosity, 6) Love the homeland, 7) Friendly/communicative, 8) Caring for the environment, 9) Social care, 10) Responsibility.Keywords: Education, Character, Novel.